Exploring the Relation Between Intuitive Physics Knowledge and Equations During Problem Solving - Buteler, Laura Maria (2014)
Solving many quantitative problems does not necessarily lead to an improved Physics understanding. However, physicists, who have learned physics largely through quantitative problems solving, often have a refined physical intuition. Assuming that the refinement of physical intuitions occurs, to a great extent, during problem solving, the question that guides this study is: how do equations contribute (or not) to the refinement of students’ intuitions? We approach this study within a knowledge-in-pieces perspective and we describe intuitions using diSessa’s (1993) phenomenological primitives. We present a study in which two cases, corresponding to two groups of students solving a problem involving buoyancy are compared. We discuss how the use of equations does or does not contribute to the refinement in students’ intuitions.